PENGARUH EKSTRAKURIKULER KEROHANIAN ISLAM TERHADAP PERILAKU SISWA DI BENGKULU - Pasmah Chandra; Nelly Marhayati; Ersa Mala Aliza (POTENSIA: Jurnal Kependidikan Islam, 2020)
The study is aimed at seeing how extracurricular Islamic spirituality affects student’s behavior at SMA Negeri 10 Bengkulu. The kind of research that is quantitative research with a quantitative descriptive approach. The data-collection techniques of questionnaire, observation, interview and documentation. The sample in this study is all of the students who have participated in extracurricular Islamic Spirituality at SMA Negeri 10 Bengkulu. Researchers use probability sampling techniques of simple random sampling. Research data analysis using simple linier regression analysis, F-Test, t-test and coefficient determinations (R2) with help of SPSS 16. The finding of this studies extracurricular activities of Islamic spirituality affect student’s behavior. This is evidenced by tcount of 3,120 whereas  ttable of 2,037 at a significant level of 0.05. Based on these results tcount is greater than the excpectation tchart. Thus, it may be concluded that Ha was accepted and Ho is rejected so that there is an influence of Islamic spirituality extracurricular activities on student behavior by 22.8% while the remaining 77.2% is influenced by other factors not studied in this study.